The Effect of Broccoli Sprout Extract on Seasonal Grass Pollen-Induced Allergic Rhinitis - Yusin, Joseph (Nutrients, 2021)
Patients exposed to pollutants are more likely to suffer from allergic rhinitis and may benefit from antioxidant treatment. Our study determined if patients diagnosed with grass-induced allergic rhinitis could benefit from broccoli sprout extract (BSE) supplementation. In total, 47 patients were confirmed with grass-induced allergic rhinitis and randomized to one of four groups: group 1 (nasal steroid spray + BSE), group 2 (nasal steroid spray + placebo tablet), group 3 (saline nasal spray + BSE) and group 4 (saline nasal spray + placebo tablet). Peak Nasal Inspiratory Flow (PNIF), Total Nasal Symptoms Scores (TNSS) and nasal mucus cytokine levels were analyzed in samples collected before and after the 3-week intervention. Comparing before and after the intervention, PNIF improved significantly when comparing Groups 1 and 2, vs. placebo, at various time points (p ≤ 0.05 at 5, 15, 60 and 240 min) following nasal challenge, while TNSS was only statistically significant at 5 (p = 0.03), 15 (p = 0.057) and 30 (p = 0.05) minutes. There were no statistically significant differences in various cytokine markers before and after the intervention. Combining nasal corticosteroid with BSE led to the most significant improvement in objective measures.